Factors contributing to rising cesarean section rates in South Asian countries: A systematic review - Dhakal-Rai, Sulochana; van Teijlingen, Edwin; Regmi, Pramod Raj; Wood, Juliet; Dangal, Ganesh; Dhakal, Keshar Bahadur (Asian Journal of Medical Sciences, 2022)
Rising cesarean section (CS) rates are a global public health problem. The systematic review investigates key indications for performing CS and factors significantly associated with the rising rate of CS in South Asia. Primary studies in South Asia published between January 2010 and December 2018 were searched using relevant electronic databases: MEDLINE, Scopus, PubMed, Web of Science, CINAHL, NepJOL, and BanglaJOL. A narrative synthesis of the indications for performing CS and factors significantly associated with the rising CS rates was performed using content analysis. A total of 68 studies were included in this review. The most common medical indication for CS was fetal distress, followed by previous CS, antepartum hemorrhage (including placenta previa/abruption), cephalopelvic disproportion, failed induction, hypertensive disorders in pregnancy, oligohydramnios, and non-progress of labor. Maternal request was the most common non-medical indication for conducting CS. Higher maternal age was the most common significant factor associated with the rising CS rate followed by higher maternal education, urban residency, higher economic status, previous CS, pregnancy/childbirth complications, and lower parity/nulliparity. Preference for CS and increasing private number hospital were also factors contributing to the rising rate. Several key indicators and factors significantly associated with rising CS rate are revealed. These key indicators and significant factors reflect the global trend. Reduction in the use of primary CS, unless medically warranted, would help stem rates of CS. Realistic and candid explanation to pregnant women and their families regarding the benefits of vaginal birth for women and babies should form an integral part of maternity care as these are issues of public health.